Validation of Finasteride Tablets USP by HPLC Isocratic with UV Detector (International Journal of Scientific Research in Science and Technology, 2025)
The aims of this work were to validate the analytical method, and evaluate the fenasteride in bulk drug commercial products by HPLC. Fenasteride was eluted from a Kromasil ODS C18, 150 mm x 4.6 mm, 5 at laboratory temperature (30 ± 2º C) with a mobile phase consisting of Acetonitrile and 2.5M Ortho phosphoric acid (50:50 %v/v) at a flow rate of 1.0 mL/min with UV detection at 240 nm. The retention time was about 3.45 minutes and each analysis took not more than 8 minutes. The result obtained for each parameter including Specificity, System Precision, Method Precision (Repeatability), Intermediate precision (Ruggedness), Solution stability, Filter Paper Interference and System suitability lies well within the acceptance criteria. Blank preparation and Placebo preparation did not show any interference at the retention time of Finasteride and peak purity of main peak in Standard preparation, Test preparation and Test spiked preparation is 1000. Ruggedness of the method was evaluated under intermediate precision and results were found within acceptable limits. The presented methods were validated (regarding ICH guidelines) and statistically compared by applying the t-test and F-test with the reported method. The proposed validated methods were found to be sensitive, selective, and can be successfully used for quality control test. Since the results are within acceptance criteria for all parameters, therefore the method is considered as validated and suitable for intended use.